NFC Technology in Public Transport - Eva Brumercikova; Bibiana Bukova; Leszek Krzywonos (Communications - Scientific letters of the University of Zilina, 2016)
This article discusses the possibility of the application of the NFC technology as a system of selling tickets in public transport. The NFC (Near Field Communication) technology is a wireless and contactless technology of transmission of radio data over short distances (max. 5 cm).